CERMINKAN SEMANGAT DAN NILAI-NILAI YANG INGIN DITANAM DALAM PAK REMAJA - Sri Dewita Br Purba Girsang; Satia Febryanti Banurea; Damayanti Nababan; Kristiel Mega Simbolon (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
“Adolescent Christian Religious Education” is an initiative that aims to reflect the spirit and values that it wants to instill in the younger generation. This program is designed to empower teenagers with the knowledge, skills and attitudes needed to become strong, responsible individuals and contribute positively to society. The spirit promoted by “Pak Teen” is the spirit of continuous growth and learning. We believe that every teenager has untapped potential, and through a holistic approach, we are committed to helping them develop their abilities to the full. The values we instill in this program include: Independence: We encourage teenagers to be independent, emotionally and financially independent, so that they can face life’s challenges with confidence. Empathy and Openness: We teach the importance of understanding and respecting differences, as well as being a good listener and empathizing with others. Leadership and Collaboration: We empower teens to become effective leaders, but also to be able to work together in teams and build strong relationships with others. Integrity: We emphasize the importance of acting in accordance with correct moral and ethical values, even when faced with pressure or temptation. Creativity and Innovation: We encourage teens to think outside the box, develop new ideas, and create solutions to complex problems. “Adolescent Christian Religious Education” is not just an educational program, but also a community where teenagers can learn, grow and support each other. By uniting these spirits and values, we hope to form a young generation who is ready to face the future with optimism and courage.